Journey to the Center of the Cell: Cytoplasmic and Nuclear Actin in Immune Cell Functions - Record, Julien; Saeed, Mezida B.; Venit, Tomas; Percipalle, Piergiorgio; Westerberg, Lisa S. (Frontiers in Cell and Developmental Biology, 2021)
Actin cytoskeletal dynamics drive cellular shape changes, thereby linking numerous cell functions to physiological and pathological cues. Mutations in actin regulators which are differentially expressed or enriched in immune cells cause severe human diseases known as primary immunodeficiencies underscoring the importance of efficienct actin remodelling in immune cell homeostasis. Here we discuss recent findings on how immune cells sense mechanical properties of their environement. While the organisation and biochemical regulation of cytoplasmic actin have been extensively studied, actin regulation in the nucleus is a rapdily emerging field and has only begun to be explored in immune cells. Based on the critical role of actin regulation in the cytoplasm, nuclear actin regulation is anticipated to have a large impact on our understanding of immune cell development and function.